(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The goal of the current study is to better identify the research experience and skills of LIS professionals working in higher education at RTM Nagpur University in Nagpur. Almost 550 colleges (granted and non-granted) in Nagpur, Bhandara, Gondia, and Wardha are connected with RTMNU, Nagpur, which includes four districts. According to the survey, funding organizations and academic institutions should step forward to support LIS professionals who want to engage in research and publishing. This will make more people want to do research at academic institutions and help them get the best library services possible.